Profile of Mind Mapping Utilization in Learning During 2018-2022 - Anggy Ayu Maharrany; Tukiran; Sunu Kuntjoro (IJORER : International Journal of Recent Educational Research, 2022)
Mind mapping is an innovative learning strategy that has an impact on learning. This research aims to define and analyze the use of mind mapping in learning. This research is qualitative-descriptive with library research type. The results of the research show that the use of mind mapping not only has advantages, but also various disadvantages when used in learning. To minimize these weaknesses, this research reviews 20 journals (2018-2022) both nationally and those that have been selected through Google Scholar. The steps in reviewing the research literature are collecting journals/articles about mind mapping, reducing journals/articles for the last five years (2018-2022), analyzing the definition of mind mapping, synthesizing the opportunities and impacts of using mind mapping in learning, analyzing obstacles to mind mapping utilization in learning, and making conclusions. Based on library research, it is found that one way for teachers and students to maximize learning is by designing mind mapping with other learning models or tools. Another finding is that teachers can use various applications to make it easier for students to make mind maps. With this research, it is hoped that learning will be fun and improve students' thinking skills.